2023
DOI: 10.3390/plants12122372
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in the Use of Wild Medicinal Plants in Trentino–South Tyrol, Northern Italy

Giulia Mattalia,
Felina Graetz,
Matthes Harms
et al.

Abstract: Mountain regions are fragile ecosystems and often host remarkably rich biodiversity, and thus they are especially under threat from ongoing global changes. Located in the Eastern Alps, Trentino–South Tyrol is bioculturally diverse but an understudied region from an ethnobotanical perspective. We explored the ethnomedicinal knowledge of the area from a cross-cultural and diachronic perspective by conducting semi-structured interviews with 22 local inhabitants from Val di Sole (Trentino) and 30 from Überetsch–Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…However, in order to minimize the limitations related to differences in the applied methodologies between our study and the study from 1970 (e.g., differences in the reported species and the availability of specific species), we conducted a comparison based on the genera level rather than the species level. Additionally, the recorded plant reports were also qualitatively compared with the most comprehensive worldwide wild food-plant compendia [ 5 , 7 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to minimize the limitations related to differences in the applied methodologies between our study and the study from 1970 (e.g., differences in the reported species and the availability of specific species), we conducted a comparison based on the genera level rather than the species level. Additionally, the recorded plant reports were also qualitatively compared with the most comprehensive worldwide wild food-plant compendia [ 5 , 7 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional ecological knowledge (TEK) is vital for local communities and their well-being. TEK has been a focal point of research within the ethnobiological field, and recent developments have witnessed a shift towards a diachronic approach that emphasizes the historical evolution of these corpora of knowledge [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The TEK of mountain communities has received more attention in the past decades because of the crucial role of mountains in providing multiple services (i.e., water, pastures/dairy products, timber and non-timber forest products, and leisure) to both highland and lower-land dwellers and urban visitors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, where industrial agriculture and subsequent urbanization are underlying the reduction in direct experiences with nature, the creation of opportunities for more local, personal, and sensory experiences is seen as a leverage point in reshaping environmental education [166]. Logically, the introduction of local knowledge for such educational purposes would serve its revitalization, but in an updated form that reflects contemporary developments in science [167].…”
Section: Online Questionnairementioning
confidence: 99%
“…Modern pharmacology stems from traditional uses of medicinal plants, and based on current biomedical research, many biologically active compounds are clearly related to specific uses known for centuries as well as new ones [168]. Fast implementation of these new data allows the development of new medicines and functional foods that reach the market, and through advertisement and targeted promotion, supplies patients and consumers with transformed and upgraded traditional knowledge that they can combine with their own [167]. Screening of medicinal use of O. basilicum in the Balkans recorded during ethnopharmacological studies revealed quite varied, relatively low popularity (use value 0.17-0.3) that corresponds to frequencies of medicinal use of sweet basil reported by our participants [76,[169][170][171].…”
Section: 12 X For Peer Reviewmentioning
confidence: 99%
“…Diachronic approach in ethnobotanical studies has recently gained the attention of several authors. The use of historical sources allows researchers to collect valuable information about the mechanisms of transmission of Local Ecological Knowledge (LEK) and the nature of its transformation over time [ 1 , 2 , 3 ]. However, the interpretation of the results from diachronic studies is complicated by the intrinsic nature of LEK consisting of a complex multifaceted corpus of different practices, beliefs, and traditions having different origin and developmental patterns, molded by different socio-ecological factors.…”
Section: Introductionmentioning
confidence: 99%